Situacion del manejo forestal sostenible en la Amazonia boliviana - Camacho, O.=700 1 Guzman, R.; Peña Claros, L.
(En, Es)
ilus., 8 ref.
Keywords: ORDENACION FORESTAL; LEGISLACION; CERTIFICACION; SOSTENIBILIDAD; AMAZONIA; BOLIVIA; COSTA RICA